2012
DOI: 10.1128/jvi.06517-11
|View full text |Cite
|
Sign up to set email alerts
|

Wild-Type Measles Virus with the Hemagglutinin Protein of the Edmonston Vaccine Strain Retains Wild-Type Tropism in Macaques

Abstract: A major difference between vaccine and wild-type strains of measles virus (MV) in vitro is the wider cell specificity of vaccine strains, resulting from the receptor usage of the hemagglutinin (H) protein. Wild-type H proteins recognize the signaling lymphocyte activation molecule (SLAM) (CD150), which is expressed on certain cells of the immune system, whereas vaccine H proteins recognize CD46, which is ubiquitously expressed on all nucleated human and monkey cells, in addition to SLAM. To examine the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…In the rhesus monkeys infected with measles virus, suppression of IL-12 in the sera was reported (20). The induction of IFN-␥, IL-2, and MCP-1 in the sera of the measles virus-infected cynomolgus monkeys was also reported (21). However, comparable levels of upregulation in proinflammatory cytokines, chemokines, and anti-inflammatory responses of IL-1 receptor antagonist observed in the CDV-infected monkeys were not reported for the measles virus-infected monkeys.…”
Section: Discussionmentioning
confidence: 93%
“…In the rhesus monkeys infected with measles virus, suppression of IL-12 in the sera was reported (20). The induction of IFN-␥, IL-2, and MCP-1 in the sera of the measles virus-infected cynomolgus monkeys was also reported (21). However, comparable levels of upregulation in proinflammatory cytokines, chemokines, and anti-inflammatory responses of IL-1 receptor antagonist observed in the CDV-infected monkeys were not reported for the measles virus-infected monkeys.…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, vaccine MV infects nectin-4-expressing cell lines with an efficiency similar to that of wild-type strains (14). Remarkably, a wild-type virus expressing the vaccine H protein still replicates preferentially if not exclusively in lymphoid (SLAM-expressing) and respiratory (nectin-4-expressing) tissues in vivo (47), implying dominance of entry through the natural receptors for MV spread.…”
Section: Discussionmentioning
confidence: 98%
“…routes (7), where the attenuated virus targeted the same CD150-expressing cells as the wild type, and infection of CD46-expressing cells was observed at a very low level. Another study where the H glycoprotein of a wild-type strain of MV was replaced with that from an attenuated strain, which could use CD46 as an entry receptor in vitro, found that replacement of the H gene did not change the tropism of the virus in macaques, where mainly CD150 ϩ infected cells were detected after infection (41). It is also in accordance with our previous studies in macaques infected with the wild-type KhartoumSudan (KS) strain of MV (6), where we identified alveolar macrophages and DCs as the early target cells of wild-type MV when administered via the aerosol route.…”
Section: Fig 3 Target Cells Of Rmv Ez Egfp(3) Egfp Distribution In Mmentioning
confidence: 99%